2019
DOI: 10.1111/febs.14934
|View full text |Cite
|
Sign up to set email alerts
|

TET enzymes control antibody production and shape the mutational landscape in germinal centre B cells

Abstract: Upon activation by antigen, B cells form germinal centres where they clonally expand and introduce affinity‐enhancing mutations into their B‐cell receptor genes. Somatic mutagenesis and class switch recombination (CSR) in germinal centre B cells are initiated by the activation‐induced cytidine deaminase (AID). Upon germinal centre exit, B cells differentiate into antibody‐secreting plasma cells. Germinal centre maintenance and terminal fate choice require transcriptional reprogramming that associates with a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 64 publications
(137 reference statements)
4
37
0
Order By: Relevance
“…Although an immunodeficiency phenotype has not been reported for Tet2-KO mice, recent studies imply a crucial role for TET2 in maintaining T-cell homeostasis and B-cell development. 38,52,53 In agreement with the mouse KO model, in which TET2 deficiency and subsequent 5hmC reduction affected differentiation of T-cell subsets, 54 we detected relative loss of Th subsets (Tfh, Th1, and Th17), with a skew toward the Th2 fate and preservation of Treg numbers. Abnormal Treg proliferation and Foxp3 destabilization were observed only after double Tet2/Tet3-KO in mice.…”
Section: Discussionsupporting
confidence: 85%
“…Although an immunodeficiency phenotype has not been reported for Tet2-KO mice, recent studies imply a crucial role for TET2 in maintaining T-cell homeostasis and B-cell development. 38,52,53 In agreement with the mouse KO model, in which TET2 deficiency and subsequent 5hmC reduction affected differentiation of T-cell subsets, 54 we detected relative loss of Th subsets (Tfh, Th1, and Th17), with a skew toward the Th2 fate and preservation of Treg numbers. Abnormal Treg proliferation and Foxp3 destabilization were observed only after double Tet2/Tet3-KO in mice.…”
Section: Discussionsupporting
confidence: 85%
“…Expression of TET1 is drastically reduced in pro-B-cells (Cimmino et al, 2015 ), while expression of TET2 and TET3 increases progressively over B-cell maturation and during activation (Schoeler et al, 2019 ). Tet-mediated 5hmC accumulation in B-cells was shown to occur within gene bodies (Cimmino et al, 2015 ; Schoeler et al, 2019 ) and at enhancer regions (Lio et al, 2016 ; Orlanski et al, 2016 ), additionally correlating with H3K4me1 histone modifications and increased transcriptional activity (Lio et al, 2016 ; Orlanski et al, 2016 ). Loss of TET1 in hematopoietic stem cells promotes differentiation with a lymphoid bias (Cimmino et al, 2015 ).…”
Section: Tet Proteins In Immune Cell Development and Diseasementioning
confidence: 99%
“…TET2 and TET3 proteins regulate somatic hypermutation (SHM) and CSR through Tet-dependent upregulation of Activation Induced Deaminase (AID) in activated B-cells (Lio et al, 2019a ; Schoeler et al, 2019 ). These studies showed that TET proteins were recruited to two sites within the AID super-enhancer, TetE1 and TetE2 (Lio et al, 2019a ), by the basic leucine zipper transcription factor, ATF-like (BATF) (Lio et al, 2019a ; Schoeler et al, 2019 ).…”
Section: Tet Proteins In Immune Cell Development and Diseasementioning
confidence: 99%
“…In B cells, loss of TET enzymes resulted in impaired class switch recombination, a process by which antibody switch from IgM to other isotypes. 61,67,88 Mechanistically, TET2 and TET3 cooperate with transcription factor Basic leucine zipper transcription factor (BATF) to promote the expression of activation-induced cytidine deaminase, the key enzyme for antibody maturation. 67 Tet2 deficiency resulted in increased germinal center B cells and decreased plasma cell differentiation after immunization.…”
Section: Tet Methylcytosine Oxidasesmentioning
confidence: 99%